PENGEMBANGAN MEDIA PRESENTASI INTERAKTIF PADA MATERI KEANEKARAGAMAN FLORA DAN FAUNA DI INDONESIA KELAS IV SEKOLAH DASAR - Rofif Nu'man Nur Robbani; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an interactive presentation media on the topic of Indonesian flora and fauna diversity for fourth-grade elementary school students. The study employed a Research and Development (R&D) method using the 4D model, consisting of the Define, Design, Develop, and Disseminate stages. The media was developed using Canva and Canva Code by integrating learning materials, instructional videos, interactive maps, navigation features, and interactive quizzes into a single learning medium. The feasibility of the product was evaluated through media expert and material expert validation, while user responses were collected through a limited implementation involving fourth-grade elementary school students. The validation results showed scores of 92% from the media expert and 94% from the material expert, both categorized as highly valid. Student responses indicated that the media was attractive, easy to use, and helpful in understanding the learning material. Therefore, the developed interactive presentation media is considered feasible to be used as an alternative learning medium for science and social studies (IPAS) learning in elementary schools.